Prevalence of end stage renal disease and associated conditions in hemodialysis Iraqi patients - Dhaidan, Fuad Abdullah (International Journal of Research in Medical Sciences, 2018)
Background: Chronic Kidney Disease (CKD) is the third most common non-communicable disease throughout the world. Most of the patients with chronic kidney disease suffer from hypertension, diabetes and with glomerulonephritis. Many of these CKD patients ultimately terminate to End Stage Renal Disease (ESRD) when life is not sustainable unless hemodialysis is initiated. This study was to identify systemic and renal disease leading to ESRD requiring hemodialysis and associated co-morbidities. Methods: Data was collected from three selected three hemodialysis centers in three hospitals during one-year study in Iraq. Patients were selected purposively who were available at the time of interview. Data was collected on working days at three shifts. these data collected from patients and their relatives in these centers after taking informed consent from patients the pre-tested questionnaire was filled up by taking general history, family history, socioeconomic condition, drug history and available records were reviewed for collecting previous biochemical parameters. All entered data were analyzed by using SPSS program. Results: Among total 400 subjects, male was 260 (65%) and female 140 (35%). Majority of patients were middle aged. Glomerulonephritis were found to be the leading cause of End Stage Renal Disease (ESRD) (50.4%), followed by diabetes in 31.1%, Poly Cystic Kidney Disease (PKD) 5.3%, Renal Stone in 3.7% and rest other. Among the study population hypertension was the most common co morbidity disease (63%) followed by ischemic heart disease and Cerebrovascular accidents. Conclusions: The leading cause of End Stage Renal Disease (ESRD) was the glomerulonephritis and diabetic nephropathy was the second common cause. Hypertension was the most common associated co morbid disease.